Shallow-water Ascidians from Matua Island (central Kuril Islands, NW Pacific), part 2 - Sanamyan, Karen; Sanamyan, Nadya (Zootaxa, 2017)
The paper reports several ascidians, previously not known from central group of Kurile Islands, including two new species, Synoicum polyzoinum n. sp. and Aplidium matua n. sp. In order to systematize our knowledge on numerous members of these genera, reported from NW Pacific, we provide an overview of all Synoicum and Aplidium species, known from Far Eastern Seas of Russia, including comments on the species erroneously identified in the past.